VD_FINDINFO AI 379/23 - 332/2024 vom 18. Oktober 2024 - VD Tribunal cantonal (2024)
EXPERTISE MÉDICALE, FORCE PROBANTE, MÉTHODE MIXTE D'ÉVALUATION | 28 LAI, 28a LAI, 29 al. 1 LAI, 4 al. 1 LAI, 27bis RAI, 88a RAI